2018
DOI: 10.2174/1570180815666180531102555
|View full text |Cite
|
Sign up to set email alerts
|

Fasciola Hepatica Extract Induces Cell Death of Mammalian Cells

Abstract: Background Fascioliasis is a neglected tropical disease that affects poor people from poor and developing countries. In the world, it has been estimated that at least 2.6 million people are affected with this disease. The International agency for Research on Cancer, states that O. viverrini and C. sinensis, also liver flukes, are considered as definitive causes of cholangiocarcinoma. However, fascioliasis caused by F. hepatica has not been associated with cancer to date. There are not any known causative assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
1
5
0
1
Order By: Relevance
“…In contrast, infection or crude extract of Trichinella spiralis has been shown to have a protective role in carcinogenesis (Wang et al, 2009). Similarly, E. granulosus and Fasciola hepatica infection also has been associated with antitumor effect (Ferreira et al, 2018; Rostami Rad et al, 2018); however, the detailed mechanism is still illusive. Thus, the field is still wide open for further exploration before ascertaining their role in cancer.…”
Section: Cestodes and Nematodesmentioning
confidence: 99%
“…In contrast, infection or crude extract of Trichinella spiralis has been shown to have a protective role in carcinogenesis (Wang et al, 2009). Similarly, E. granulosus and Fasciola hepatica infection also has been associated with antitumor effect (Ferreira et al, 2018; Rostami Rad et al, 2018); however, the detailed mechanism is still illusive. Thus, the field is still wide open for further exploration before ascertaining their role in cancer.…”
Section: Cestodes and Nematodesmentioning
confidence: 99%
“…hepatica extracts could have a potential as a preventive or even curative anti-cancer substance [9,10].…”
Section: The "Cancer Hygiene Hypothesis" Explainedmentioning
confidence: 99%
“…In order to develop an effective vaccine strategy, it is important to understand the key immunological features that the parasite triggers in the mammalian host. It has been shown that stimulation with liver fluke-derived extracts, such as excretory/secretory (ES) products and tegument, induce unbalanced Th1/Th2 responses (1113), alternative activation of macrophages (14) and cell death (15). In addition, glycoconjugates derived from liver fluke extracts induce activation of peritoneal eosinophils (16) and apoptosis of macrophages (17).…”
Section: Introductionmentioning
confidence: 99%